Observability and predictability in quantum and post-quantum physics - Fankhauser, J (2022)
I introduce a framework to distinguish two domains of physics - the manifest (i.e. the directly observable empirical records in terms of manifest configurations) and the non-manifest domain of physics (i.e. the things that the manifest configurations signify according to a physical theory). I show that many quantum 'paradoxes' rest on ambiguous reasoning about the two domains. More concretely, I study so-called 'surrealistic' trajectories, the 'delayed choice quantum eraser', and 'weak measurements'. Finally, I show how the alleged puzzles resolve in the framework provided.